Education, equality and human rights : issues of gender, 'race', sexuality, disability and social class - Cole, Mike, 1946- (Abingdon, Oxon ; New York, NY : Routledge, 2018)
'Education, Equality and Human Rights' addresses the issue of human rights and its relationship to education in the 21st century. Each of the five equality issues of gender, race, sexuality, disability and social class are covered as areas in their own right, and in relation to education.
Introduction : human rights and equality legislation and education / Mike Cole -- Unfinished business : women still unequal after all this time / Jane Kelly -- Gender and education : perspectives through time / Jane Martin -- Racism in the UK : continuity and change / Mike Cole -- Racism and education : from Empire to May / Mike Cole -- Sexualities, identities and equal rights : the making and remaking of sexualities / Simon Forrest -- Time for straight talking : challenges and opportunities in teaching and learning about sexuality and homophobia in schools / Simon Forrest -- Achieving disability equality : the continuing struggle / Richard Rieser -- Inclusive education : implementing human rights / Richard Rieser -- Social class, Marxism and socialism / Mike Cole -- Mystification of production and feasibility of alternatives : social class inequality and education / Alpesh Maisuria.
Includes bibliographical references and index.
Keywords: Educational equalization -- Great Britain; Discrimination in education -- Great Britain; Human rights; Critical pedagogy -- Great Britain; Critical pedagogy; Discrimination in education; Educational equalization; Human rights; Great Britain